1995
DOI: 10.1523/jneurosci.15-05-04033.1995
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of neuronal nitric oxide synthase (NOS) in visceral neurons after nerve injury

Abstract: The distribution of nitric oxide synthase immunoreactivity (NOS-IR) and the changes in this distribution after peripheral axotomy were examined in lumbosacral afferent and preganglionic neurons (PGNs) innervating the pelvic viscera of the male rat. The visceral neurons in L6-S1 and L1-L2 dorsal root ganglia (DRG) and in the spinal cord were identified by retrograde axonal transport following injection of Fluorogold (FG) into the major pelvic ganglion (MPG). Axotomy was performed by removing the MPG on one side… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
77
1
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(94 citation statements)
references
References 54 publications
15
77
1
1
Order By: Relevance
“…Double ICC confirmed that GRP-containing fibers surrounded neurons expressing neuronal nitric oxide synthase (nNOS; Fig. 1m-u), a marker for autonomic preganglionic neurons 14 and an enzyme involved in erection and ejaculation 12 . Electron micrography demonstrated GRP-immunoreactive presynaptic boutons innervating nNOS-positive dendrites in these autonomic nuclei of the lumbosacral spinal cord (Fig.…”
mentioning
confidence: 73%
“…Double ICC confirmed that GRP-containing fibers surrounded neurons expressing neuronal nitric oxide synthase (nNOS; Fig. 1m-u), a marker for autonomic preganglionic neurons 14 and an enzyme involved in erection and ejaculation 12 . Electron micrography demonstrated GRP-immunoreactive presynaptic boutons innervating nNOS-positive dendrites in these autonomic nuclei of the lumbosacral spinal cord (Fig.…”
mentioning
confidence: 73%
“…Spinal cord segments were identified based on at least two criteria as follows: 1) the T 13 dorsal root ganglion (DRG) exits after the last rib and 2) the L 6 vertebra is the last moveable vertebrae followed by the fused sacral vertebrae. Segmentation was later confirmed by immunostaining the autonomic nucleus in the L 6-S1 spinal segments with neuronal nitric oxide synthase (nNOS) IR (64). Our previous work (64) demonstrated that all nNOS IR cells in the rat SPN were retrogradely labeled from the major pelvic ganglion and therefore represented preganglionic parasympathetic neurons.…”
Section: Immunohistochemistrymentioning
confidence: 92%
“…Segmentation was later confirmed by immunostaining the autonomic nucleus in the L 6-S1 spinal segments with neuronal nitric oxide synthase (nNOS) IR (64). Our previous work (64) demonstrated that all nNOS IR cells in the rat SPN were retrogradely labeled from the major pelvic ganglion and therefore represented preganglionic parasympathetic neurons. Only spinal segments exhibiting nNOS IR in the autonomic nucleus were subsequently used in analysis, and all rats in the present study exhibited nNOS-immunoreactive cell bodies in the L6-S1 autonomic nucleus.…”
Section: Immunohistochemistrymentioning
confidence: 92%
“…NADPHd and NOS protein are inducible in term of de novo synthesis in traumatically injured neurons (Wu, 2000). After peripheral axotomy, NOS protein and NOS mRNA increase in some neuronal populations (Verge et al, 1992;Vizzard et al, 1995); moreover, NOS is up-regulated in axotomized motoneurons (Yu, 1994;Yu, 1997;Mü ller and Stoll, 1998;Ma et al, 2000).…”
Section: Nos Induction After Axotomymentioning
confidence: 99%
“…In the mammal cerebellum, Purkinje cells normally do not contain NOS (Vincent, 1994;Blottner et al, 1995;Vincent, 1996), but a lesion can induce NADPHd in the perikaria (Blottner et al, 1995;Saxon and Beitz, 1996). Increased NOSi and NADPHd activity were described in dorsal root ganglia on the ipsilateral side to peripheral axotomy (Vizzard et al, 1995), from 3 days to 4 weeks. Similar results were obtained after electrolyte lesions of the nucleus basalis magnocellularis (Sabbatini et al, 1999).…”
Section: Nos Induction After Axotomymentioning
confidence: 99%